Integration of Islamic Values in the Project Based Learning Model and its Relevance to the Strengthening of Scientific and Religious Literacy - Sanjaya, Nia Rahayu; Harahap, Muhammad Yunan (Al-Fikru: Jurnal Ilmiah, 2025)
This research is motivated by the challenges in integrating science and religious literacy in vocational high school. The purpose of this study is to describe the implementation of Islamic values-based Project-Based Learning (PBL) model to improve science and religious literacy at Al Karomah Berastagi Private Vocational School. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation studies. The results showed that the implementation of PBL was carried out systematically through planning, implementation, reflection, and presentation, with the integration of Islamic values in each stage. This implementation improved students' mastery of scientific concepts, critical thinking skills, and the application of science in daily life. Students' religious literacy also develops through the understanding of Qur'anic verses relevant to science, as well as the internalization of spiritual values and religious practices. The role of teachers, school support, and the involvement of the social environment are important factors in the success of this model. Although there are obstacles, cross-subject collaboration strategies can be an effective solution. The implication of this research shows that Islamic values-based PBL can be an effective model for integrating science and religious literacy and promoting holistic learning in schools.